Rancang Bangun Alat Monitor Detak Jantung Dan Suhu Tubuh Berbasis Android - Agung Gamara; Atika Hendryani (Jurnal Sehat Mandiri, 2019)
The heart is a vital organ that must always be kept healthy. Not only the heart, body temperature is also important to control the condition of the body with the environment and know the symptoms of serious illness.Heart rate and body temperature are very important parameters to determine a person's health condition. The importance of monitoring these two parameters so that we need gauges that are easy to use and carry so that they can always monitor the values of the two parameters within normal limits. The purpose of this research is to design and build an Android-based Heart Rate and Body Temperature Monitor.The methods used are literature study, tool design and interface, testing tools, and analyzing test results. Arduino Nano-based heart rate and body temperature detector uses Max 30100 sensor as a measurement of heart rate and DS18B20 sensor as body temperature sensor. The sensor readings will be processed by Arduino Nano which will be displayed on LCD 16 x 2 and Android.The test results show that the heart rate and body temperature monitoring tools function properly with an accuracy value of 99.1% for measuring heart rate and 99.4% for measuring body temperature. Suggestions as a consideration for developing this research next is to make the android display easier and have health information and what should be done by a system user related to heart rate and body temperature.